Semiconductor colloidal quantum dots for photovoltaic applications - Cheng, C (2014)
This thesis studies lead suphide (PbS) colloidal quantum dots and their photovoltaic applications. Different sizes of PbS QDs were synthesised and characterised using absorption spectroscopy and transmission electron microscopes. PbS QD Schottky junction devices were fabricated with AM1.5 power conversion efficiency up to 1.8 %. The Schottky junction geometry limits the device performance. A semiconductor heterojunction using ZnO as an electron acceptor was built and the device efficiency increased to 3%. By studying the light absorption and charge extraction profile of the bilayer device, the absorber layer has a charge extraction dead zone which is beyond the reach of the built-in electric field. Therefore, strategies to create a QD bulk heterojunction were considered to address this issue by distributing the junction interface throughout the absorber layer. However, the charge separation mechanism of the QD heterojunction is not clearly understood: whether it operates as an excitonic or a depleted p-n junction, as the junction operating mechanism determines the scale of phase separation in the bulk morphology. This study shows a transitional behaviour of the PbS/ZnO heterojunction from excitonic to depletion by increasing the doping density of ZnO. To utilise the excitonic mechanism, a PbS/ZnO nanocrystal bulk heterojunction was created by blending the two nanocrystals in solution such that a large interface between the two materials could facilitate fast exciton dissociation. However, the devices show poor performance due to a coarse morphology and formation of germinate pairs. To create a bulk heterojunction where a built-in electric field could assist the charge separation, a TiO2 porous structure with the pore size matching with the depletion width was fabricated and successfully in-filled by PbS QDs. The porous device produces 5.7% power conversion efficiency, among one of the highest in literature. The enhancement comes from increased light absorption and suppression of charge recombination.